2018
DOI: 10.1021/acschembio.8b00127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and Regulation of the Ergothioneine Biosynthetic Methyltransferase EgtD

Abstract: Ergothioneine is an emerging factor in cellular redox homeostasis in bacteria, fungi, plants, and animals. Reports that ergothioneine biosynthesis may be important for the pathogenicity of bacteria and fungi raise the question as to how this pathway is regulated and whether the corresponding enzymes may be therapeutic targets. The first step in ergothioneine biosynthesis is catalyzed by the methyltransferase EgtD that converts histidine into N-α-trimethylhistidine. This report examines the kinetic, thermodynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 77 publications
1
19
0
Order By: Relevance
“…For heterologous production of S. cerevisiae TRP5, E. coli KRX transformed with pJF56 was used. Production of E. coli S ‐adenosylhomocysteine nucleosidase and adenine deaminase followed a described procedure . The above enzymes were purified by immobilized metal‐affinity chromatography on a His Trap FF Crude column (1 mL bed volume), fitted to an Äkta Pure 25 FPLC instrument (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…For heterologous production of S. cerevisiae TRP5, E. coli KRX transformed with pJF56 was used. Production of E. coli S ‐adenosylhomocysteine nucleosidase and adenine deaminase followed a described procedure . The above enzymes were purified by immobilized metal‐affinity chromatography on a His Trap FF Crude column (1 mL bed volume), fitted to an Äkta Pure 25 FPLC instrument (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…In more recent work, it has been suggested that ERG was probably first biosynthesised by anaerobes using a slightly different route that converts hercynine directly to ERG (98)(99)(100) , and that was later repurposed. Three-dimensional structures are known for a number of the relevant enzymes, including mycobacterial EgtB (101) for example, PDB 4XBE, EgtC (102) for example, PDB 4ZFJ, EgtD (103)(104)(105) for example, PDB 4PIM, and Neurospora crassa early G1 transcript 2 (egt2) which is like egtE (106) for example, PDB 5UTS.…”
Section: Biosynthesis and Phylogenetic Distributionmentioning
confidence: 99%
“…Of note, the residues of EgtD known to interact with the (methylated) α‐amino group of l ‐histidine, that is, Gly161 and Asn166, are conserved in TrpM (Gly192 and Asn197). Asn166 in EgtD is essential to make N , N ‐dimethyl‐ l ‐histidine a 100‐fold stronger ligand than l ‐histidine . Crystallographic work would be warranted to elucidate the respective roles of the active‐site residues for TrpM.…”
Section: Methodsmentioning
confidence: 99%